Entanglement fidelity of quantum memories - Surmacz, K; Nunn, J; Waldermann, F; Wang, Z; Walmsley, I; Jaksch, D (American Physical Society, 2006)
We introduce a figure of merit for a quantum memory which measures the preservation of entanglement between a qubit stored in and retrieved from the memory and an auxiliary qubit. We consider a general quantum memory system consisting of a medium of two level absorbers, with the qubit to be stored encoded in a single photon. We derive an analytic expression for our figure of merit taking into account Gaussian fluctuations in the Hamiltonian parameters, which, for example, model inhomogeneous broadening and storage time dephasing. Finally we specialize to the case of an atomic quantum memory where fluctuations arise predominantly from Doppler broadening and motional dephasing.